THE INFLUENCE OF INTELLIGENCE QUOTIENT AND EMOTIONAL QUOTIENT TOWARD EMPLOYEE PERFORMANCE (CASE STUDY AT PT. BANK MANDIRI (PERSERO) TBK. MANADO BRANCH OFFICE WANEA) - Kojongian, Rivan A. (Jurnal Berkala Ilmiah Efisiensi, 2016)
ABSTRACT The performance of employees determined the success of a company and the achievement of company objectives, and therefore a company need their employees are able to show optimal performance because performance will affect the overall success of the company or organization.Â  This research was conducted by using quantitative analysis method. The main objectives in this research are: (1)To know the influence of intelligence quotient toward employee performance at PT.Bank Mandiri (Persero) tbk. Manado Brach Office Wanea (2) To know the influence of intelligence quotient toward employee performance at PT.Bank Mandiri (Persero) tbk. Manadi Brach Office Wanea. Sample of this research is 30 respondents. The results from the study showed that the intelligence quotient and emotional quotient has significantly influence employee performance , as well as the factors that influence most dominantÂ  is emotional quotient. Keywords: Intelligence Quotient, Emotional Quotient, Employee Performance